2017
DOI: 10.1038/ismej.2017.45
|View full text |Cite
|
Sign up to set email alerts
|

Allelopathic interactions of linoleic acid and nitric oxide increase the competitive ability of Microcystis aeruginosa

Abstract: The frequency and intensity of cyanobacterial blooms are increasing worldwide with major societal and economic costs. Interactions between toxic cyanobacteria and eukaryotic algal competitors can affect toxic bloom formation, but the exact mechanisms of interspecies interactions remain unknown. Using metabolomic and proteomic profiling of co-cultures of the toxic cyanobacterium Microcystis aeruginosa with a green alga as well as of microorganisms collected in a Microcystis spp. bloom in Lake Taihu (China), we … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
52
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 124 publications
(52 citation statements)
references
References 40 publications
0
52
0
Order By: Relevance
“…Disentangle when the observed growth responses are caused by allelochemicals or by the costs associated to the production of compounds is an important and critical question but would require further investigations on the nature of released compounds. Our experiment is consistent with other studies showing that exudates of Microcystis can influence the physiology of other cyanobacteria (Bartova et al ., ; Yang et al ., ; Maria et al ., ) or green algae (Bittencourt‐Oliveira et al ., ; Ma et al ., ; Dunker et al ., ; Song et al ., ; Wang et al ., ). Exposure of Microcystis strains may result in various effects on the targeted organism ranging from alteration of growth and cellular morphology, photosynthesis, changes in pigment, protein, increased formation of reactive oxygen species, activation of gene expression or cell lysis.…”
Section: Discussionmentioning
confidence: 99%
“…Disentangle when the observed growth responses are caused by allelochemicals or by the costs associated to the production of compounds is an important and critical question but would require further investigations on the nature of released compounds. Our experiment is consistent with other studies showing that exudates of Microcystis can influence the physiology of other cyanobacteria (Bartova et al ., ; Yang et al ., ; Maria et al ., ) or green algae (Bittencourt‐Oliveira et al ., ; Ma et al ., ; Dunker et al ., ; Song et al ., ; Wang et al ., ). Exposure of Microcystis strains may result in various effects on the targeted organism ranging from alteration of growth and cellular morphology, photosynthesis, changes in pigment, protein, increased formation of reactive oxygen species, activation of gene expression or cell lysis.…”
Section: Discussionmentioning
confidence: 99%
“…After 96 h, Chlorella vulgar cells in both the control and the maximum concentration of Fenhexamid were harvest and then the sample was fixed using 2.5% glutaraldehyde at 4 o C for 12 h. The fixed cells were washed and dehydrated using a graded series of ethanol (35, 50, 70, 90 and 100%) and then embedded in epoxy resin, following the method described by Song et al (2017), then observed using a JEOL JSM 1400-plus model transmission electron microscope (TEM) and JEOL JSM 6510 model scanning electron microscope (SEM).…”
Section: Cellular and Subcellular Structure Observationmentioning
confidence: 99%
“…In order to understand the allelopathic effect of combined materials and to receive a more reactive natural herbicide, binary mixtures of seven natural molecules (containing a variety of functional groups), namely R -(+)-limonene ( A ) [ 23 , 24 , 25 ], vanillin ( B ) [ 26 , 27 , 28 , 29 , 30 ], xanthoxyline ( C ) [ 11 ], vanillinic acid ( D ) [ 28 , 31 , 32 , 33 , 34 , 35 ], linoleic acid ( E ) [ 36 , 37 , 38 , 39 ], methyl linoleate ( F ) [ 40 , 41 , 42 , 43 ], and (±)-odorine ( G ) [ 12 , 13 ] ( Figure 1 ), were investigated using Chinese amaranth ( Amaranthus tricolor L.) as the test plant and Tween ® 80 as a surfactant. Chinese amaranth was chosen as a representative dicot plant because it has a high percentage of germination.…”
Section: Introductionmentioning
confidence: 99%